Dimensi Metrik Graf Kincir K1+nK3 - Amrullah, Amrullah; Soeprianto, Harry; Sarjana, Ketut; Hayati, Laila (FKIP Universitas Mataram, 2024)
The metric dimension is a fundamental concept in graph theory that utilizes the vector representation of distances between vertices and a subset of vertices in a graph. This concept has broad applications in various fields, such as navigation, network localization, and network design. Let G(V,E) be a connected graph with order n . A subset L=v1,v2,v3 subset of V(G) is called a resolving set, and the representation of a vertex v with respect to L is a vector (d(v,v1), d(v,v2)..d(v,vk)) , where d(v,vi) is the distance between v and vi . The metric dimension of G, denoted as dim(G), is the smallest cardinality of L such that every vertex in G has a unique representation. The windmill graph K1+nK3 is a graph obtained by connecting a vertex x in the complete graph K1 to every vertex in n copies of the complete graph K3. This paper employs a structural analysis method focused on the single vertex in K1 and determines the vector representations of all vertices in the windmill graph by analyzing inter-vertex distances. The final result shows that the metric dimension, dim (K1+nK3)= 2n, where n is an integer grether than 2 .